Informe de SITUACIÓN FITOSANITARIA - Región Centro Norte de Córdoba 19 de febrero de 2016 - De Rossi, R.; Guerra, F; Lábaque, M.; Vuletic, E; Brücher, E.; Plazas, M. C.; Guerra, G.D. (Informe de Situación Fitosanitaria, 2018)
Ninguno